Association of neutrophil-to-albumin ratio with all-cause and cardiovascular mortality in community-dwelling individuals with chronic kidney disease: evidence from the NHANES 1999–2018 - Yu Han; Xiaocui Jiao; Mingyue Yang; Chao Liu; Deyun Zhao (BMC Cardiovascular Disorders)
Abstract Background The relationship between the neutrophil percentage-to-albumin ratio (NPAR) and all-cause mortality as well as cardiovascular disease (CVD) mortality, in individuals with chronic kidney disease (CKD), remains unclear. This study aimed to elucidate the association between NPAR and mortality risks in CKD individuals. Methods The study analyzed a prospective cohort of CKD individuals from the National Health and Nutrition Examination Survey (NHANES) spanning the years 1999 to 2018. Cox proportional hazards regression model estimated the hazard ratios and 95% confidence intervals to assess the association between NPAR and the risk of all-cause and CVD mortality. Restricted cubic spline (RCS) analysis was conducted to investigate potential nonlinear relationships and segmented Cox proportional hazards regression models were used to evaluate threshold effects. Additionally, stratified analyses were performed to examine the relationship between NPAR and mortality across different subgroups. Results The study include 3,029 community-dwelling CKD individuals. Higher NPAR were significantly associated with increased risks of both all cause and CVD mortality. RCS analysis indicated J-shaped non-linear correlations between NPAR and both all-cause mortality and CVD mortality. Below threshold values (11.60 for all-cause and 12.29 for CVD mortality), increasing NPAR was associated with a decreased risk for both types of mortality. However, beyond these thresholds, elevated NPAR were found to correlate with increased mortality risks. Stratified analyses suggested the relationship between NPAR and mortality remained consistent across most subgroups, except for the race subgroup. Conclusions NPAR were significantly associated with the risks of all-cause and CVD mortality in community-dwelling individuals with CKD. It suggested NPAR is a valuable tool for predicting the risk of mortality in CKD individuals.